2021
DOI: 10.31219/osf.io/jhsfc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Language contact within the speaker: Phonetic variation and crosslinguistic influence

Abstract: A recent model of sound change posits that the direction of change is determined, at least in part, by the distribution of variation within speech communities (Harrington, Kleber, Reubold, Schiel, & Stevens, 2018; Harrington & Schiel, 2017). We explore this model in the context of bilingual speech, asking whether the less variable language constrains phonetic variation in the more variable language, using a corpus of spontaneous speech from early Cantonese-English bilinguals (Johnson, Babel, Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
(187 reference statements)
0
1
0
Order By: Relevance
“…For example, using single word productions, Cantonese-English bilinguals characterized as Cantonese heritage speakers were more likely to release word-final stops [13]. Conversely, a recent study of the same phenomenon in spontaneous speech found that early Cantonese-English bilinguals were less likely to release final stops in English than non-Cantonese-English bilinguals [20]. These conflicting outcomes simply illustrate the need to examine variation in speech across styles and registers, as this variation has maximum utility for ASR systems and the development of NLP tools for speech and language, given how little is know about how talkers interact with such systems [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, using single word productions, Cantonese-English bilinguals characterized as Cantonese heritage speakers were more likely to release word-final stops [13]. Conversely, a recent study of the same phenomenon in spontaneous speech found that early Cantonese-English bilinguals were less likely to release final stops in English than non-Cantonese-English bilinguals [20]. These conflicting outcomes simply illustrate the need to examine variation in speech across styles and registers, as this variation has maximum utility for ASR systems and the development of NLP tools for speech and language, given how little is know about how talkers interact with such systems [21].…”
Section: Introductionmentioning
confidence: 99%